2018
DOI: 10.1051/matecconf/201824602004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Grey Clustering Method Based on Improved Analytic Hierarchy Process in Water Quality Evaluation

Abstract: To highlight the differences in water quality impacts of different indicators in water samples, this paper proposes a grey clustering method based on improved analytic hierarchy process to evaluate the quality of surface water. According to the pollution degree of different indicators in the water quality sample, the importance score is assigned, and the weight of different indicators is calculated by the analytic hierarchy process. The weight participates in the calculation of the grey clustering coefficient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…In this case, Shannon Entropy could have been applied alternatively, as was done in the present study, to calculate these weights in an objective and precise way. Similarly, in the study carried out by Wang et al [12] the clustering weights could be obtained through the Shannon Entropy method and be complemented by the Single Factor method used in this study.…”
Section: A Results On the Case Studymentioning
confidence: 99%
“…In this case, Shannon Entropy could have been applied alternatively, as was done in the present study, to calculate these weights in an objective and precise way. Similarly, in the study carried out by Wang et al [12] the clustering weights could be obtained through the Shannon Entropy method and be complemented by the Single Factor method used in this study.…”
Section: A Results On the Case Studymentioning
confidence: 99%
“…In addition, in the assessment of water bodies in the Rimac River [9], they mention that the monitoring points belong to Category 1 A2-Population and Recreation using the Grey Clustering method, so the methodology is similar to the Peruvian RCTs [4], Therefore, in our study, when the results of the application of the Grey Clustering and the results of the participatory monitoring in the 12 monitoring points were compared, in fact it was evident that they complied with the RCT on water [4] in 11 of the points, and in P6 they did not comply with national standards, thus inferring that the results obtained were much more reliable. Finally, this method was used because according to the study conducted on the water quality of the Qingshui River in the city of Duyun, China [10], and compared to the results produced by other methods, it turns out to be more scientific and reasonable and can provide a basis for the evaluation of water quality and the management of the water environment in any space where it is carried out.…”
Section: A About the Methodologymentioning
confidence: 99%
“…In the research paper entitled "Application of Grey Clustering Method Based on Improved Analytic Hierarchy Process in Water Quality Evaluation", they proposed a Grey Clustering method based on an improved analytical hierarchy process to evaluate the water quality of the Qingshui River in Duyun City, by sampling three water periods (periods of abundant, normal and deficient flow) in 4 sections of the river. It was concluded that the water quality of the river belongs to the superclass III according to its regulations, and according to this the contamination is not serious [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the focus of this method is located within the artificial intelligence that is related to the study of problems with little or limited sample information [9]. Which is the reason why the Grey Clustering method has a wide range of applicability such as problem optimization [10], social impact assessment [11], investment risk decision [12] and water quality studies [13]. Furthermore, it is very important to emphasize that traditional methods cannot develop a complex non-linear equation between standard parameters and water quality grades, since there are many factors that modify water quality.…”
Section: Introductionmentioning
confidence: 99%